Isolation of Bacillus spp. Bacteria from Soil for Production of Cellulase - Manzum, Amika Ahmed; Mamun, Md Arafat Al (Nepal Journal of Biotechnology, 2019)
Cellualse is one of the most important enzymes used in textile, detergent, paper, food and feed industries. Therefore, a study was undertaken to isolate Bacillus bacteria having the potential to produce cellulase from soil samples. 24 soil samples were analyzed and 54 presumptive Bacillus isolates were isolated after heating the soil samples at 80°C for 10 min. Among them 45 isolates showed enzyme activity ranging from 0.003 to 0.17 U/ml in test tubes containing 5 ml medium composed of (g/L) glucose 0.5 gm, peptone 0.75 gm, FeSO4 0.01 gm, KH2PO4 0.5 gm, and MgSO4 0.5 gm at 120 rpm, 37° C and pH 7. Among them 1RW, 2WS, 3YR, 4WT, 6 RR, and 9SS showed 0.17, 0.15, 0.14, 0.15, 0.147 and 0.14U/ml enzyme activities, respectively. Production of cellulase by these isolates was further scaled up to shake culture containing 50 ml medium similar to that used in test tube culture. Among the isolates 1 RW showed the maximum activity. This 1 RW was identified by API kit and showed that 59 % belongs to Bacillus licheniformis strain (51% confirmation) or Bacillus subtilis (31% confirmation). Further gene analysis is required to confirm the species. The genetic improvement study will make the isolate a good source of cellulase.